Origin of the ahead of tsunami traveling ionospheric disturbances during Sumatra tsunami and offshore forecasting. Issue 7 (21st July 2017) - Bagiya, Mala S.; Kherani, E. A.; Sunil, P. S.; Sunil, A. S.; Sunda, S.; Ramesh, D. S.
Abstract: The presence of ionospheric disturbances associated with Sumatra 2004 tsunami that propagated ahead of tsunami itself has previously been identified. However, their origin remains unresolved till date. Focusing on their origin mechanism, we document these ionospheric disturbances referred as Ahead of tsunami Traveling Ionospheric Disturbances (ATIDs). Using total electron content (TEC) data from GPS Aided GEO Augmented Navigation GPS receivers located near the Indian east coast, we first confirm the ATIDs presence in TEC that appear ~90 min ahead of the arrival of tsunami at the Indian east coast. We propose here a simulation study based on tsunami‐atmospheric‐ionospheric coupling that considers tsunamigenic acoustic gravity waves (AGWs) to excite these disturbances. We explain the ATIDs generation based on the dissipation of transverse mode of the primary AGWs. The simulation corroborates the excitation of ATIDs with characteristics similar to the observations. Therefore, we offer an alternative theoretical tool to monitor the offshore ATIDs where observations are either rare or not available and could be potentially important for the tsunami early warning. Key Points: Traveling ionospheric disturbances appeared at Indian east coast before ~90 min of the arrival of 26 December 2004 Sumatra tsunami Identification of the generation mechanism of tsunami traveling ionospheric disturbances that propagated ahead of Sumatra tsunami Proposing an alternative tool to monitor the offshore ahead of tsunami traveling ionospheric disturbances